Local government failure in Australia? An empirical analysis of New South Wales - Bymes, Joel; Dollery, Brian (2002)
The complexities of contemporary local governance in Australia and other advanced democracies provide social scientists with significant theoretical and empirical callenges. Drawing on recent developments, including public choice theory, economists have sought to develop taxonomic systems of government failure specifically tailored to local govefrnment circumstances. This paper seeks to extend the Dollery and Wallis (2001b) taxonomy of local government failure by invoking Olson's (1965) concept of political entrepreneurship. The paper then attempts to determine the empirical validity of the augmented taxonomy by examining it in the context of NSW local government. - Reproduced.
Keywords: Local government - Australia; Local government